Kesepadanan Tekstual dan Ideologi Penerjemahan Arab-Jawa dalam Kitab Sharḥ al-Ḥikam - Muhammad Yunus Anis (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
This study attempts to elaborate textual equivalence of the Arabic translation and the Javanese translation in Ibn ‘Aṭā’ Allah al-Sakandarī’s masterpiece, al-Ḥikam. Within the first stage, the texts in this book will be studied from many linguistic aspects connected to lexical forms and phraseological features. Every language is semantically assumed as possessing specific characteristic in terms of its lexical and phraseological features. The Sufis, in this case, will have a particular inclination in their language expression. The lexical and phraseological features become, among others, a measurement of mystical language which covers compositional and unitary meanings. To comprehensively understand the mystical life explained in al-Ḥikam we need, therefore, to deeply study such lexical and phraseological features. The second stage will focus on the ideology of translation of al-Ḥikam. This sort of ideology will provide us with information on the relation of the Indonesian Islamic texts and—along with their potential integration with—scholars around the world. The study finds that the ideology of translation has been founded on foreignization method and domestication method. These two methods have played a pivotal role on how particular texts of Sufisme are produced and consumed by the Indonesian Muslim society.